Reforming Graduate Medical Education in Syria: A Strategic Framework for Post-Conflict Recovery - Sbei, Oase; Rass, Amjad; Alomar, Abd Arrahman; Muhbeddine, Ahmed; Sankari, Abdulghani (Avicenna Journal of Medicine, 2025)
More than a decade of armed conflict has devastated Syria's healthcare system, severely disrupting graduate medical education (GME) across the country. Damage to teaching hospitals, displacement of faculty, and fragmented oversight have contributed to deteriorating educational standards and a growing physician shortage. As Syria transitions into a post-conflict recovery phase, reforming its GME system is a national and global priority.This white paper aims to evaluate the current state of GME in Syria and propose a strategic framework for rebuilding a standardized, sustainable, and internationally aligned system through stakeholder engagement, data collection, and comparative analysis.In February 2025, the Syrian American Medical Society (SAMS) conducted workshops in Damascus and Aleppo involving over 45 stakeholders, including teaching hospital directors, medical educators, and diaspora physicians. A pre-workshop survey assessed program structure, oversight, curricula, evaluation methods, and infrastructure across 21 institutions. Workshop discussions were informed by a Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis and global best practices from countries including Jordan, Saudi Arabia, and the United States.Findings revealed wide variability in program oversight, clinical training quality, evaluation standards, and faculty support. Only 57% of institutions reported having formal curricula, while 81% conducted some form of trainee evaluation. Common challenges included inadequate financial support, lack of standardized accreditation, insufficient faculty development, and limited research access. Recommendations from the workshops included the creation of a national accreditation council, modernization of curricula, investment in faculty training, development of centers of excellence, and integration of online education and 25 continuing medical education.Reforming Syria's GME system requires coordinated, multilevel efforts to implement competency-based education, establish independent regulatory bodies, and align training programs with global standards. The phased framework presented here offers actionable steps to rebuild Syria's medical education infrastructure and train a resilient health workforce capable of addressing both national and regional healthcare needs.
Keywords: Syria; graduate medical education; post-conflict recovery; medical training; accreditation; curriculum reform; healthcare workforce; medical education reform